Managing Coasts with Natural Solutions : Guidelines for Measuring and Valuing the Coastal Protection Services of Mangroves and Coral Reefs - World Bank Group (World Bank, Washington, DC, 2016)
This guidance note provides review and recommendations for how the protective services of mangroves and coral reefs can be measured and valued in a manner consistent with national economic accounts and included in other decision-making processes to support planning for development, disaster risk, and coastal zone management. It synthesizes evidence of the role mangroves (chapter 2) and coral reefs (chapter 3) play in coastal protection and risk reduction. It also reviews the tools and approaches commonly used by ecologists, economists, and engineers for estimating the coastal protection services of coastal habitats (chapter 4). Moreover, it examines how the valuations of these coastal protection services can be considered in the System of Environmental Economic Accounts (SEEA), the satellite accounts to the System of National Accounts (SNA) (chapter 5). In addition, the note examines where the coastal protection role of reefs and mangroves has been used in management decisions from local to national scales (chapter 6). Finally, it provides recommendations for advancing the assessment and the use of coastal protection values from coral reefs and mangroves in national and regional decisions (chapter 7).